An “Exceeding Faire” Baby in the King James Bible: A New Testament Greek Example of a Hebrew Elohim Superlative - Bell, David (The Bible translator, 2014)
Stephen, in his defense recorded in Acts 7, mentions the fact that Moses’ parents hid him against the direct command of Pharaoh to kill the baby because they saw that he was “exceeding faire” (Acts 7.20, KJV). This paper discusses the origins of this novel understanding of the Greek text ἀστεῖος τῷ θεῷ (beautiful to God), which follows neither the traditional translations which were previous to the English Bible nor the various English versions which paved the way for the KJV. Rather, the translation reflects the use of the Elohim superlative of the KJV Old Testament. It is a clear example of the influence the KJV has had on subsequent English Bible translations, both in the cases of Bibles which obviously follow the KJV’s reading as well as those traditional revisions or translations which normally follow the language and style of the KJV but in this specific case do not.